Analisis Penggunaan Metode Konversi dalam Alih Media Arsip Statis di BKAD Kabupaten Malang - Aliya Afifah Prasetya; Muhammad Iqbal (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study analyzes the use of the conversion method in the digitization of static archives at the Archives Unit of the Regional Financial and Asset Agency of Malang Regency. The research used a descriptive qualitative approach through observation, interviews, and documentation. The findings show that digitization has been implemented mainly to support access and reduce dependence on physical archives. However, its implementation has not fully met the requirements of ANRI Regulation Number 2 of 2021. Several gaps were found in human resource readiness, limited equipment, non-standardized file naming, informal quality control, the absence of official minutes, and the lack of authentication through watermark, digital signature, certificate, or hash value. Metadata management is also constrained by the inactive archival information system, although backup has been performed through online and offline storage. The study concludes that conversion-based digitization at BKAD Malang Regency is useful as an access tool, but it still needs formal procedures, authenticated digital objects, standardized metadata, and stronger institutional support to meet archival standards